OAUNI photometry of ASASSN-16hz - Pereyra, Antonio (2016)
We report optical photometry of Type Ia SN ASASSN-16hz (=SN 2016eqb, ATel #9332, ATel #9333) on 2016-08-09 (UT) gathered with the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging was performed with seeing ~1.8" and airmass = 1.3. A total integration time of 900s (45x20s) and 880s (44x20s) in R and V filter, respectively, yielded: Date (UT)